624 The Molecular Endotypes of Type 1 and Type 2 SLE. (14th December 2022) - Robl, Robert D; Eudy, Amanda M; Bachali, Prathyusha S; Rogers, Jennifer L; Clowse, Megan EB; Pisetsky, David S; Lipsky, Peter E
Abstract : Objective: To characterize the molecular landscape of patients with Type 1 and Type 2 systemic SLE erythematosus (SLE) by analyzing gene expression profiles from peripheral blood. Methods: Full transcriptomic RNA sequencing was carried out on whole blood samples from 18 subjects with SLE selected by manifestations of Type 1 and Type 2 SLE as determined by SLE Disease Activity Index (SLEDAI) and Polysymptomatic Distress (PSD) score, respectively. The top 5, 000 row variance genes were analyzed by a suite of gene expression technologies to generate gene coexpression modules which were functionally annotated and correlated to various demographic traits, clinical features and laboratory assays. Results: Stable k-means clustering of gene coexpression modules effectively segregated Type 1 from Type 2 SLE. Unique Type 1 SLE enrichments included IFN, neutrophils, monocytes, IL-1, TNF, cell cycle, and neurotransmitter pathways, whereas unique Type 2 SLE enrichments included B cells, plasma cells, Ig chains, and neuromuscular pathways. Enrichment of the IFN signature was not observed in Type 2 SLE. Gene expression patterns of some Type 2 SLE patients were identified amongst gene expression profiles reported in the literature for inactive SLE and idiopathic fibromyalgia (FM) patients. Conclusion: A suite of orthogonal gene coexpression technologies successfully identified unique transcriptional patterns that segregate Type 1 SLE from Type 2 SLE, and further identified Type 2 molecular features in patients with inactive SLE or FM.